Suitability of Chlorella ellipsoidea as food for production of the rotifer Brachionus calyciflorus - Akter, S; Shahjahan, M; Rahman, MS; Das, PS (International Journal of Agricultural Research, Innovation and Technology, 2014)
Rotifers are valuable live food for larval fish and crustacean in aquaculture. In the present study, we conducted an experiment to evaluate the suitability of Chlorella ellipsoidea as food for production of the rotifer, Brachionus calyciflorus. The experiment was carried out in three treatments using dried powder Chlorella ellipsoidea (T1), fresh live Chlorella ellipsoidea (T2) and Bakers yeast (T3) as food with three replications. For supplying food to rotifers, C. ellipsoidea was cultured sufficiently in different inexpensive culture media before rotifer culture and it was continued up to the end of the rotifer culture experiment. The ranges of environmental factors analyzed were suitable for both C. ellipsoidea and rotifers culture during the experimental period. Maximum cell densities of C. ellipsoidea were recorded in inexpensive pulse bran extract medium during the culture period. The mean population densities (means ± SEM) of B. calyciflorus were significantly (p<0.01) highest in T2 (28.6 ± 4.64 (x103) individuals L-1) compared to T1 (11.6 ± 1.24 (x103) individuals L-1) and T3 (11.4 ± 1.82 (x103) individuals L-1). The findings of present study revealed that fresh cultured C. ellipsoidea was the best food for production of the rotifer, B. calyciflorus. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17843 Int. J. Agril. Res. Innov. & Tech. 3 (2): 41-48, December, 2013